L’implication des acteurs dans l’implantation de projets d’amélioration des situations de travail en ergonomie participative : des constats différenciés dans deux usines - Sylvie Montreuil; Micheline Marier; Marie Bellemare; Johanne Prévost; Denis Allard (Perspectives Interdisciplinaires sur le Travail et la Santé)
A participatory ergonomics intervention was conducted for two years in two plants owned by a major metal-producing company. The objective of the intervention was the prevention of musculoskeletal disorders (MSDs) by making use of the capacity of the people in the plants to analyze and modify work situations considered as hazardous. The results presented in this paper focus on the intervention process and the transformation projects. They show that a site with more centralized operations, more homogeneous production activities, and a better defined role for its steering committee produced a higher rate of completed workplace modification projects. However, projects with increased productivity and MSD prevention were easier to carry out. The discussion addresses the importance of a clear position by decision-makers about the completion of the projects and about the contribution of this type of process for training ergonomics intermediaries within such workplaces.